Rhythms of Love - Johnson, Doris (Bet Publication ltd, 2002)
An attack left dancer Brynn Halsted injured in both body and spirit. When handsome jazz club owner Simeon Storey challenges her to recover her self-worth at his Poconos retreat, Brynn can't resist the offer--or the simmering attraction between them. Now with her career and future in the balance, Brynn must risk it all to claim her dreams.
Keywords: Juvenile literature-Myths and legends-Children's stories-Chivalry-Romance-Fiction